Pyloric Brunner's gland hamartoma with atypical hyperplasia - Luciano Lenz; Aloisio Felipe-Silva; Frank Nakao; Nelson Miyajima; Ermelindo Della Libera; Dalton Marques Chaves; Beatriz Monica Sugai; Maria Rachel da Silveira Rohr (University of São Paulo, 2013)
Brunner's gland hamartoma (BGH) is an extremely rare benign digestive tumor, generally located in the duodenal bulb. We report the case of a 51-year-old asymptomatic man with a large pedunculated BGH arising from the pylorus. It was successfully removed en bloc by endoscopic resection.